Implementasi blue economy dengan pendampingan pembuatan buku profil UMKM produk olahan perikanan Desa Batu Belubang, Bangka Belitung - Adibrata, Sudirman; Pratiwi, Anggelia Nurtasbita; Jesiska, Adella; Aulia, Aulia; Animah, Animah; Purnamasari, Ariska; Angelia, Fera; Rani, Indah Septia; Anggraini, Nadilla (Indonesia Berdaya, 2022)
Village Development Activity 2022 conducted a real contribution to promoting micro, small, and medium enterprises (UMKM) at Batu Belubang Village, Pangkalan Baru Sub-district, Central Bangka Regency, Kepulauan Bangka Belitung Province. Optimizing the marine resources by the UMKM to bolster the economy and entrepreneurship at the village is in accord with the blue economy concept. Some optional solutions to UMKM problems found in the village like introducing the business concept of fishery product processing that belongs to IPAL, eye-catching product packaging, gradually permitting assistance by related government bodies, knowledge transfer, and digital marketing via Facebook, WhatsApp, Instagram, Twitter, an official virtual store like Bukalapak, Shopee, and others. The guidance and assistance of UMKM from the local government regarding the potential of processed fishery products is very much needed. One of the assistances is the creation of a profile book for processed fishery products UMKM to facilitate the path of information to consumers. A website-based information technology network is very helpful in promoting UMKM for fishery products that can reach consumers from across provinces in Indonesia and across countries. Abstrak: Kegiatan Bina Desa tahun 2022 dapat memberikan konstribusi nyata untuk memajukan UMKM di Desa Batu Belubang Kecamatan Pangkalan Baru Kabupaten Bangka Tengah Provinsi Kepulauan Bangka Belitung. Mengoptimalkan sumberdaya laut untuk pertumbuhan ekonomi dan wirausaha di desa sejalan dengan konsep blue economy. Tawaran solusi dari permasalahan UMKM di Desa Batu Belubang yaitu pengenalan konsep usaha pengolahan hasil perikanan yang memiliki IPAL, kemasan produk yang lebih menarik perhatian (eye catching), perijinan diharapkan dapat dibantu oleh dinas terkait secara berkala, transfer pengetahuan dan keterampilan pemasaran digital seperti Facebook, Whattsap, Instalgram, Twitter, toko virtual yang resmi seperti Bukalapak, Shopee dan lainnya. Pembinaan dan pendampingan UMKM dari pemerintah daerah terkait potensi produk olahan hasil perikanan sangat dibutuhkan. Salah satu pendampingan yaitu pembuatan buku profil UMKM produk olahan perikanan untuk mempermudah jalur informasi ke konsumen. Jaringan teknologi informasi berbasis website sangat membantu promosi UMKM produk perikanan yang dapat menjangkau konsumen dari lintas provinsi di Indonesia dan lintas negara.